Severe Cutaneous Adverse Drug Reactions : A Prospective Study Of Epidemiology And Clinical Pattern. (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Cutaneous adverse drug eruptions are the most common adverse reactions  attributed to drugs in which any type of skin reaction can be mimicked, induced, or  aggravated. Cutaneous drug reactions are of wide range from mild to moderate to severe life  threatening reactions. The term severe cutaneous adverse drug reactions encompasses Steven– Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), drug reaction with eosinophilia and  systemic symptoms (DRESS), and acute generalized exanthematous pustulosis (AGEP). Aims: The aims of this study are to evaluate the clinical and epidemiological aspects of severe  cutaneous adverse drug reactions (SCADRS) at a tertiary care center from gujarat. Methods : This is a prospective study which was conducted over period from September 2014  to December 2016. A total 31 patients were included in the study which included outpatients as  well as inpatients admitted after written informed consent.The diagnosis of SJS, TEN ,AGEP  were made on clinical grounds and according to standard definitions while in case of DRESS  REGISCAR score was used to establish the diagnosis. Results : In the study, a total of 31 patients were included in the study,in which 18 were males  and 13 were females, and maximum patients were in the age group of 31-40 years. SJS  14(45.16%) was the most common SCADR. Antiepileptic class of drug was found to be most  commonly implicated.  Conclusion : Patients can be educated to avoid re-administration of the offending drug(s) to  reduce the morbidity associated with CADRs. Early identification of SCADRs can reduce the  morbidity and mortality rates.
Keywords: Steven–Johnson syndrome; toxic epidermal necrolysis